The TNNT2:c.95‐108G>A variant is common in Maine Coons and shows no association with hypertrophic cardiomyopathy. (30th May 2022) - Schipper, Tom; Ohlsson, Åsa; Longeri, Maria; Hayward, Jessica J.; Mouttham, Lara; Ferrari, Paolo; Smets, Pascale; Ljungvall, Ingrid; Häggström, Jens; Stern, Joshua A.; Lyons, Leslie A.; Peelman, Luc J.; et al.
Abstract: Hypertrophic cardiomyopathy (HCM) is a common and potentially fatal heart disease in many cat breeds. An intronic variant in TNNT2, c.95‐108G>A, was recently reported as the cause of HCM in the Maine Coon. The aim of this study was to determine this variant's allele frequency in different populations and its possible association with HCM. Based on 160 Maine Coon samples collected in Belgium, Italy, Sweden and the USA, the variant's allele frequency was estimated to be 0.32. Analysis of the 99 Lives feline whole genome sequencing database showed that the TNNT2 variant also occurs in other breeds, as well as mixed‐breed cats. Comparison of 31 affected and 58 healthy cats did not reveal significantly increased odds for HCM in homozygotes. Based on the combined evidence and in agreement with the standards and guidelines for the interpretation of sequence variants, this variant is currently classified as a variant of unknown significance and should not be used for breeding decisions regarding HCM.